Reproduction-Associated Hormones and Adult Hippocampal Neurogenesis - Lily Wan; Rou-Jie Huang; Zhao-Hui Luo; Jiao-e Gong; Aihua Pan; Jim Manavis; Xiao-Xin Yan; Bo Xiao (Neural Plasticity)
The levels of reproduction-associated hormones in females, such as estrogen, progesterone, prolactin, and oxytocin, change dramatically during pregnancy and postpartum. Reproduction-associated hormones can affect adult hippocampal neurogenesis (AHN), thereby regulating mothers' behavior after delivery. In this review, we first briefly introduce the overall functional significance of AHN and the methods commonly used to explore this front. Then, we attempt to reconcile the changes of reproduction-associated hormones during pregnancy. We further update the findings on how reproduction-related hormones influence adult hippocampal neurogenesis. This review is aimed at emphasizing a potential role of AHN in reproduction-related brain plasticity and its neurobiological relevance to motherhood behavior.